Impact of Religiosity, Work-related Stress on Job Performance and Workload as Moderating Variable - R. Iqbal Robbie; R. Tanzil Fawaiq Sayyaf (International Journal of Social Science and Business, 2022)
Islamic banks are a combination of conventional and sharia practices carried out in banking operations, different cultures will give birth to a dynamic condition. The main problem as described above is that employee performance is identical to Islamic values, this is caused by too much workload so that they have to continue to work beyond reasonable working hours or overtime. The number of employees who are absent due to various reasons. This study examines how religiosity, work stress on employee performance, and the effect of workload moderating variables on the relationship between religiosity and performance in Islamic banks in Pasuruan City. Data were distributed through questionnaires and in-depth interviews to 70 employees of Islamic Banks in Pasuruan City, East Java Province, Indonesia. Data collection through questionnaires was processed with SmartPLS data analysis. The results showed that religiosity had a positive and significant effect on work stress and employee performance, job stress had no significant effect on performance, and workload as a moderating variable weakened the influence of religiosity on employee performance.